PENGARUH PEMBERIAN MAKANAN TAMBAHAN PEMULIHAN (PMT-P) TERHADAP PERTUMBUHAN BALITA BAWAH GARIS MERAH (BGM) DI PUSKESMAS KOTA WILAYAH SELATAN KEDIRI - Hari Poernomo, Dewi Ika Sari; Anggraeni, Santi (Jurnal Penelitian STIKES Kediri, 2011)
ABSTRACT Â Less nutrition in under five years children was manifested of less weight and growth with under red line influence brain development, it is very close relationship to mental development and thinking capability. Because of sufficient nutrient will create human resources who have health, cleverness, activeness and productivity. Less nutrition in this age effects in disorder that can delay further development. Giving recovered supplementary food correctly, in purpose, to add intake nutrient in under five years children with under red line besides giving daily food, so that the growth will not be in under red line any more. The objective was to prove if there was influence of giving recovered supplementary food toward the growth of under five years children with under red line in Puskesmas Kota Wilayah Selatan Kediri. Design used in this research was one-group pre-post test design. The sample was 18 respondents using total sampling technique. The variable was the growth of under five years children with under red line were measured by portable balances scale (dacin) with significant range in 0,1 kg. The data was collected and then analyzed using Wilcoxon signed ranks with level of significance of Î±